2018
DOI: 10.1177/0020764018792592
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic attainments and suicidal ideation by age groups in Korea

Abstract: The information about suicidal ideation was obtained from only one question of self-response, which limits the validity of the suicidal ideation measurement. The cross-sectional setting of the data prevents us from estimating causal relationships. Nevertheless, the findings imply that age-specific policy should be implemented to ameliorate differential risk for suicidal ideation and benefit public mental health in the long run.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…Our results showed that the association between depressive symptoms and suicidal ideation was stronger in adolescents with a low socioeconomic status. These findings, in line with previous research [ 39 , 40 , 41 ], indicate that a low family socioeconomic status may be a risk factor for the emergence and maintenance of some internalizing problems. These results may help us to identify vulnerable populations and evidence the convenience of developing primary prevention programs designed to target non-referred adolescents who come from economically disadvantaged family contexts.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results showed that the association between depressive symptoms and suicidal ideation was stronger in adolescents with a low socioeconomic status. These findings, in line with previous research [ 39 , 40 , 41 ], indicate that a low family socioeconomic status may be a risk factor for the emergence and maintenance of some internalizing problems. These results may help us to identify vulnerable populations and evidence the convenience of developing primary prevention programs designed to target non-referred adolescents who come from economically disadvantaged family contexts.…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting finding is that when both socioeconomic status and parents’ educational level were considered in the same analysis, suicidal ideation was significantly associated with socioeconomic status, but not with parents’ educational level. As predicted, and consistent with available evidence [ 40 , 41 ], we found higher levels of suicidal ideation among referred and non-referred adolescents from families with a low socioeconomic status. In contrast, the relationship between socioeconomic status and depressive symptoms was not significant when parents’ educational level was partialled out.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among the three other studies, unemployment was significantly associated with suicidal ideation in the study by Yi and Hong [ 67 ], but not in the study by Kim and Yoon [ 39 ], whereas Moon and Park [ 58 ] observed a higher likelihood for suicidal ideation in relation to unemployment for women only.…”
Section: Resultsmentioning
confidence: 90%